2021
DOI: 10.1101/2021.12.22.473948
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Estimating Microbial Population Data from Optical Density

Abstract: The spectrophotometer has been used for decades to measure the density of bacterial populations using the turbidity expressed as optical density – OD. However, the OD alone is an unreliable metric and is only proportionately accurate to cell titers to about an OD of 0.6. The relationship between OD and cell titer depends on the configuration of the spectrophotometer, the length of the light path through the culture, the size of the bacterial cells, and the cell culture density. We demonstrate the importance of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…The difference between the mean OD was significant (p<0.05). OD values are an indirect measurement of bacterial growth and activity within a microenvironment (Mira et al, 2022) and as such, directly corresponded with the bacterial counts reported for the bacterial isolates during the shakeflask experiment. The axenic Bacillus sp.…”
Section: Growth Profile Studymentioning
confidence: 76%
“…The difference between the mean OD was significant (p<0.05). OD values are an indirect measurement of bacterial growth and activity within a microenvironment (Mira et al, 2022) and as such, directly corresponded with the bacterial counts reported for the bacterial isolates during the shakeflask experiment. The axenic Bacillus sp.…”
Section: Growth Profile Studymentioning
confidence: 76%
“…Fitness as a measure of reproductive potential is primarily evaluated using bacterial growth rates 70,71,72 . The density of the microbial culture is directly proportional to the optical density (OD), however, this is only true for a limited OD range, above which measuring culture density with high precision can be demanding 73 . Additionally, external factors affecting the morphology of bacterial cells, like filamentation, elongation or clumping of cells can interfere with OD measurements, thereby affecting growth rate measurements 74,75 .…”
Section: Discussionmentioning
confidence: 99%
“…However, most require coding skills, such as GrowthCurver 1 , Grofit 2 or growthrates 3 and some are closed-source commercial software (e.g. GrowthRates 4 ). To streamline the process of growth curve analysis and make it more accessible, we developed Dashing Growth Curves, an easy-to-use open-source web application.…”
Section: Introductionmentioning
confidence: 99%